Application of the SWMM model for the analysis of urban tunnel flooding in the city of Recife – PE - Silva , Maria Angélica Veiga Da; Soares , Willames de Albuquerque; Holanda , Marco Aurelio Calixto Ribeiro de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
Floods in urban centers have been recurrent, mainly in urban centers with disorderly growth and a deficient collection network. In this context, the city of Recife-PE is vulnerable to flooding in the event of moderate and heavy rainfall. Thus, the objective was to simulate the insertion of a detention reservoir in the Túnel da Abolição, located in a central area of Recife-PE, through a hydrological-hydraulic model, evaluating its effects in minimizing flooding inside the tunnel, from precipitation events that occurred in the city. For this purpose, data from the local micro-drainage system were obtained from the Recife City Hall and the parameters and variables necessary for the hydraulic-hydrological simulation were defined, such as: delimitation and characterization of the contribution areas, project rainfall and tide. Subsequently, calibration and validation of the model were carried out, which generated satisfactory results, with errors of less than 10%. However, the study site has an unfavorable flow condition, the drainage system concentrates the rainwater collected into the tunnel and the implementation of a detention reservoir, despite reducing volume and height at the control point, is not resolving. Because of this, a monitoring system was suggested as a proposal to anticipate possible pumping failures and avoid flooding.